2006
DOI: 10.1097/01.fpc.0000199501.54466.de
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the FAS and FAS ligand genes associated with risk of cutaneous malignant melanoma

Abstract: The FAS/FAS ligand (FASLG) system has a key role in regulating cell growth and thus tumorigenesis. Functional promoter polymorphisms of the FAS and FASLG genes alter the transcriptional activities, but no published study has investigated the role of these polymorphisms in the etiology of cutaneous malignant melanoma (CMM). In a hospital-based, case-control study of 602 non-Hispanic white CMM patients and 603 cancer-free age- and sex-matched control subjects, we genotyped FAS-1377G>A, FAS-670A>G, FASLG-844T>C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…A significantly associated risk was found for FAS À670 A/G polymorphism in bladder, 13 cervical cancer, 11,16,22 cutaneous malignant melanoma, 12 esophageal and head and neck squamous cell carcinoma, 15,21 lung and nasopharyngeal cancer. 9,17,20 We analyzed the frequency of FAS genotypes in the normal control population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A significantly associated risk was found for FAS À670 A/G polymorphism in bladder, 13 cervical cancer, 11,16,22 cutaneous malignant melanoma, 12 esophageal and head and neck squamous cell carcinoma, 15,21 lung and nasopharyngeal cancer. 9,17,20 We analyzed the frequency of FAS genotypes in the normal control population.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 In addition, polymorphisms in the FAS gene and perhaps also in the FASL gene that impair apoptotic signal transduction are associated with a high risk of cancer in various models. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Thus, the FAS/FASL system appears to have a role in the development and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this meta-analysis, three studies assessed the SNPs in the adjacent regions that were in linkage disequilibrium with rs763110 12,15,25 in which FASL haplotype and combined genotype analyses showed that the variant haplotypes were associated with significantly higher cancer risk. These results indicate that FASL polymorphisms may play a crucial role in the development of cancer, which is biologically plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have investigated the role of the FASL rs763110 in the etiology of cancers of various organs, including the breast, 13 -15 cervix, 16 -19 bladder, 20 lung, 21 -23 head and neck, 12 skin, 24,25 esophagus, 26 stomach, 27 ovary, 28 thymus, 29 and pancreas. 30 However, the results of these studies remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…All tumors of the patients were histologically classified according to the 2002 American Joint Committee on Cancer ''melanoma staging system'' (17). As previously described (15,16), cancer-free control subjects were also recruited during the same period from self-reported cancer-free visitors to M. D. Anderson Cancer Center who were not seeking medical care but instead accompanied patients to our outpatient clinics, and the response rate among those we approached for recruitment was f90%. The controls who were not blood related to the patients and agreed to donate a blood sample were frequency matched to the patients by age (F5 years), sex, and ethnicity.…”
Section: Methodsmentioning
confidence: 99%